Recognizing a Distinct Functional Style for Religious Texts: Implications for Linguistic Research - Yusupova Shahzoda Tohirjon qizi (Universitas Muhammadiyah Sidoarjo, 2023)
This article explores the concept of functional styles in language and suggests that a distinct functional style should be recognized for religious texts, as supported by many linguists worldwide and in Uzbekistan. The study aims to identify the characteristic aspects of this style and how it differs from other functional styles. The authors used a literature review approach to examine existing research on religious linguistics and functional styles. The findings indicate that religious texts possess unique linguistic features that differentiate them from other styles, and thus, it is necessary to study them as a separate functional style. The implications of this study are significant, as it emphasizes the importance of recognizing the religious style in linguistic research and provides a foundation for further exploration of this style in language. Highlights: The article suggests recognizing a distinct functional style for religious texts, which differs from existing styles. The study emphasizes the unique linguistic features of religious texts, which require separate examination. The need for recognizing the religious style in linguistic research is highlighted, based on existing ideas in world linguistics.